EVALUASI PREMI JOINT LIFE PASANGAN SUAMI ISTRI MENGGUNAKAN COPULA FRANK - WIDANA, I NYOMAN; ASIH, NI MADE (E-Jurnal Matematika; Vol 7 No 1 (2018)DO - 10.24843/MTK.2018.v07.i01.p181, 2018)
This paper  introduces  the joint life satatus for married  couples with independent and dependent mortality models. Using Frank copula and   Indonesia  Life Tables 2011, we evaluate the impact of dependent future lifetimes on the net single and level premium.  The results show premium rates are reduced if models of dependent future lifetime are used compared to the models using an assumption of independence.